An Industrial systems design study on Aruba Bar and Restaurant - Aquino, Diana Sylvia; Batungbakal, Pia Marie; Cruz, Jennifer; Lucero, Pinky (College of Engineering, 2005)
With the fast-paced lives of people nowadays, eating out is increasingly becoming popular due to its convenience. This is one of the major reasons why trends show that the food service industry is growing. Eating outside one's house is becoming a normal part of life. It can be observed that the restaurants are increasing in number and so are the options of food from which people can choose. On the other hand, it is a challenge for restaurants to survive the competition in the industry ? as in the case of Aruba Bar and Restaurant. The main objective of this study is to apply concepts and techniques in Industrial Systems Design, particularly Strategic Management in a practical and real life setting, particularly to a service industry. To achieve this, it was necessary to document Aruba Bar and Restaurant's products, services and processes. The restaurant industry and the competitors were also analyzed to see where the company is at present. Also, the company's strategies were determined and linked with its goals and mission. The performance of Aruba was then analyzed in relation to the company's mission and vision. This included a SWOT Analysis of the company. The strength of Aruba is having a defined target market, being accepted by its target market, having a strategic location, knowledgeable and experienced management, sociable staff, and their competitive pricing on drinks. On the other hand, lack of documentation, slow growth, limited space and lack of marketing as a restaurant are its weaknesses. Aruba's opportunity is in expansion, either through an additional branch or through a new restaurant. The threats that the company must take note of are the competitors, people's tendency to be health conscious, and the taxation of beer. The marketing strategy of the company was also analyzed. It was identified that the pricing strategy of Aruba is profit-oriented. Their key promotion strategies were through magazine articles, radio plugs, and gig plugs of bands, website listings and paid-event hosting. The wide variety of food and drinks Aruba offer is their product strategy. Lastly, choosing Metrowalk in Meralco Avenue, Pasig City was the company's place strategy. The company's financial analysis was also evaluated based on the study, the company's sales tripled from their sales in Libis. Also, a shift in the economic class of the customers was observed when they transferred. The company, with 25% of their sales prearranged as their profit, is financially stable. After the gap analysis and strategy generation, the following key strategies were identified and prioritized: expansion by opening a new branch of Aruba, improvement of service level by optimization of manpower schedule, and improvement of service level by improving inventory management. These were then translated into operational level recommendations aimed to improve customer service, increase revenues or reduce operating expenses, and raise profits. The first recommendation is the pre-feasibility of opening a new branch of Aruba in Baywalk. The existence of competitors and market were analyzed, and strategy for the marketing capacity facility planning manpower complement and suppliers were prepared. Furthermore, a new schedule on the number of waiters per day, which would generate a P7900.00 per week savings, was recommended. The number of waiters from Monday to Sunday is as follows: 7, 7, 12, 8, 15, 14 and 5. Lastly, an inventory system was also recommended. Sensitive to the fluctuations of inventory costs, the perpetual inventory system yielded lower cost than periodic order system. This inventory system is applicable to the scale of the company with the aid of simple inventory software.